The Mediation Role of Job Satisfaction in the Relationship Between Physical And Psychosocial Work Environment on Employee Retention - Anto Tulim; Purnaya Sari Tarigan; Iskandar Muda (Manunggal Halim Jaya, 2026)
Human resources are those who provide the strength, expertise, creativity, and enthusiasm to manage an organization's shared assets. This is certainly a significant asset and is crucial for company management. Employees are a vital element in a company because of their significant contribution to achieving targets and business development. To achieve optimal growth, companies need employees with high skills and strong commitment. Retaining quality employees is a crucial factor in achieving organizational goals, especially amidst increasing global competition. This study aims to analyze the influence of the physical and psychological work environment on employee retention, with job satisfaction as a mediating variable. The method used is a Structural Equation Modeling (SEM) approach based on Partial Least Squares (SmartPLS 4.0). The sample consisted of 120 permanent employees at a private university in Medan. Data were collected using a Likert-scale questionnaire. The results showed that the physical and psychological work environment significantly influenced job satisfaction, and job satisfaction mediated the relationship between the work environment and employee retention. Based on the SmartPLS results, it can be concluded that the research model has high validity and reliability, the relationship between variables is significant and strong, with an R² value indicating a feasible and stable model, and job satisfaction acts as a significant mediator, strengthening the influence of the work environment on employee retention. These results emphasize the importance of creating a physically comfortable and psychologically conducive work environment to increase employee loyalty.